2016
DOI: 10.1159/000447640
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Infant Face-to-Face Interaction: The Communicative Value of Infant-Directed Talking and Singing

Abstract: Background: Across culture, healthy infants show a high interest in infant-directed (ID) talking and singing. Despite ID talking and ID singing being very similar in physical properties, infants differentially respond to each of them. The mechanisms underpinning these different responses are still under discussion. Methods: This study explored the behavioral (n = 26) and brain (n = 14) responses from 6- to 8-month-old infants to ID talking and ID singing during a face-to-face mother-infant interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These results were subsequently replicated in 6-month-old infants (Vouloumanos, Martin, & Onishi, 2014). Even with an attention grabbing and highly natural activity such as singing, 6 to 8-month-olds display less communicative behaviors (vocalization, visual contact, body movements and synchrony of these behaviors with maternal interactive behavior) in a face-to-face interaction than with a talking mother (Arias & Pena, 2016) exchanging with ostensive social signals but one speaking and the other "beeping", 6-month-old infants become able to use the "beeps" to identify a "dinosaur" category as opposed to "fish", unlike babies who have heard the same audio file but decorrelated from the social exchanges (Ferguson & Waxman, 2016). This experiment illustrates the three key elements that support pedagogy in human infants: social cognition to figure out the communication medium, the ability to sort objects in categories, and a symbolic system to label any category.…”
Section: Speech An Information Tool On the Worldmentioning
confidence: 73%
“…These results were subsequently replicated in 6-month-old infants (Vouloumanos, Martin, & Onishi, 2014). Even with an attention grabbing and highly natural activity such as singing, 6 to 8-month-olds display less communicative behaviors (vocalization, visual contact, body movements and synchrony of these behaviors with maternal interactive behavior) in a face-to-face interaction than with a talking mother (Arias & Pena, 2016) exchanging with ostensive social signals but one speaking and the other "beeping", 6-month-old infants become able to use the "beeps" to identify a "dinosaur" category as opposed to "fish", unlike babies who have heard the same audio file but decorrelated from the social exchanges (Ferguson & Waxman, 2016). This experiment illustrates the three key elements that support pedagogy in human infants: social cognition to figure out the communication medium, the ability to sort objects in categories, and a symbolic system to label any category.…”
Section: Speech An Information Tool On the Worldmentioning
confidence: 73%
“…Very little research focused on the neurobiology of attachment from the child's end. Arias and Pena ( 2016 ) found that infants exhibited higher beta- and gamma-band activity to infant-directed speech compared to singing and suggested that episodes of personal, species-typical behavior elicit beta and gamma oscillations in areas of the affiliative brain. A study assessing brain-to-brain synchronization between infants and mothers while viewing a video of mother singing showed that maternal singing had a direct causal effect on the infant's oscillatory patterns in the theta and alpha bands.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that asymmetry differences were not driven by a specific trial type (especially given that positive trials contained both infant-directed talking and infant-directed singing, which have been shown to elicit differing behavioral patterns in infants, see Arias and Peña, 2016) F(2,18) = 3.97, ƞ p 2 = .31, p = .037, observed power = .64,…”
mentioning
confidence: 99%